EDUCATOR AND EDUCATION PLANNING IN MAN 2 MODEL MEDAN - Yahfizham Yahfizham; Ahmad Sulaiman; Riduan Pohan; Yenni Fitri (Universitas Dharmawangsa, 2020)
The Education Planner has been regulated in a law that explains that the Quality of National Education will be measured through the achievement of all National Education Standards, including Content Standards, Processes, Graduation Competencies, Education and Education Personnel, Facilities and Infrastructure, Management, Financing and Assessment (PP RI) No. 19 of 2005 has been perfected with Government Regulation No. 32 of 2013). Serious and serious attention by the parties to the efforts to fulfill and realize all these standards will determine the quality/quality of education.